Caffeine as a Lead Compound for the Design of Therapeutic Agents for the Treatment of Parkinson’s Disease - P. Petzer, Jacobus; Petzer, Anel (Current Medicinal Chemistry, 2015)
The current pharmacological therapies for the treatment of Parkinson’s disease are mostly inadequate and recent, improved therapeutic agents are required. Two important molecular targets for the design of anti-parkinsonian therapeutic compounds are the adenosine A2A receptor and the enzyme, monoamine oxidase (MAO) B. Adenosine A2A receptor antagonists are a relatively new class of anti-parkinsonian agents, which act by potentiating dopamine-mediated neurotransmission via dopamine D2 receptors. MAO-B inhibitors are established therapy of Parkinson’s disease and inhibit the MAO-B-catalysed metabolism of dopamine in the brain. This conserves reduced dopamine stores and extends the action of dopamine. A2A antagonism and MAO-B inhibition have also been associated with neuroprotective effects, further establishing roles for these classes of compounds in Parkinson’s disease. Interestingly, caffeine, a known adenosine receptor antagonist, has been recently considered as a lead compound for the design and discovery of A2A antagonists and MAO-B inhibitors. This review summarizes the recent efforts to discover caffeinederived MAO-B inhibitors. The design of caffeine-derived A2A antagonists has been extensively reviewed previously. The prospect of discovering dual-target-directed compounds that act at both targets is also evaluated. Compounds that block the activation and function of both A2A receptors and MAO-B may have a synergistic effect in the treatment of patients with Parkinson’s disease.
Keywords: inhibition